Evaluación del perfil profesional de directivos y docentes en relación al dominio de una lengua extranjera en los colegios fiscal Santa Rosa y Zoila Duarte de Landívar, periodo lectivo 2011-2012 y propuesta de un programa de educación continua en el idioma ingles fundamentado en el plan decenal de educación y la teoría sociocritica. - Aguilar Quirola, Luis Erwin Gonzalo (2013)
One of the biggest challenges of the XXI century society is education. The formation of the new generations have to raise it from the current needs , educating them to live in the knowledge society in a global world marked by international relations and a labor market that extends beyond the borders of individual countries. Each day the number of people who speak English in the world .